Electronic adherence monitoring identifies severe preschool wheezers who are steroid responsive. Issue 9 (10th July 2020) - Bingham, Yvonne; Sanghani, Nina; Cook, James; Hall, Pippa; Jamalzadeh, Angela; Moore‐Crouch, Rachael; Bush, Andrew; Fleming, Louise; Saglani, Sejal
Abstract: Little is known about adherence to inhaled corticosteroids (ICS) in preschool children with troublesome wheeze. Children with aeroallergen senitization, or those reporting multiple trigger wheeze (MTW), are more likely to respond to ICS. We hypothesized that adherence to ICS and symptom control are only positively related in atopic children, or those reporting MTW. Patients aged 1 to 5 years with recurrent wheeze prescribed ICS were recruited from a tertiary respiratory clinic. Clinical phenotype and aeroallergen senitization were determined, and adherence assessed using an electronic monitoring device (Smartinhaler). Symptom control (test for respiratory and asthma control in kids [TRACK]), quality of life (PACQLQ), airway inflammation (offline exhaled nitric oxide) were assessed at baseline and follow‐up. Forty‐eight children (mean age 3.7 years; SD, 1.2) were monitored for a median of 112 (interquartile range [IQR], 91‐126) days. At baseline n = 29 reported episodic viral wheeze and n = 19 reported MTW. Twenty‐four out of 48 (50%) wheezers had suboptimal ICS adherence (<80%). Median adherence was 64% (IQR, 38‐84). There was a significant increase in TRACK and PACQLQ in the group as a whole, unrelated to adherence. In subgroup analysis only atopic wheezers with moderate or good adherence ≥ 60% had a significant increase in TRACK. There was no relationship between clinical phenotype, and adherence or TRACK. In this pilot study, overall adherence to ICS was suboptimal and was positively related to symptom control in atopic wheezers only. Assessments of adherence are important in preschool troublesome wheezers before therapy escalation to help identify those with an ICS responsive phenotype.